Efektivitas Strategi Flash Sale dan Gratis Ongkir Terhadap Perilaku Impulsive Buying Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Islam Malang Sebagai Konsumen Online - Aldi Pratama; Agus Widarko; Muhammad Tody Arsyianto (E-JRM : Elektronik Jurnal Riset Manajemen, 2026)
Abstract The purpose of this study was to examine how digital advertising tactics, such as flash sales and free shipping, influence online impulse buying behavior among students at the Faculty of Economics and Business, Islamic University of Malang. Due to the rapid development of e-commerce, digital platforms are encouraged to use marketing techniques that emphasize financial benefits and time urgency, which can lead to impulsive purchases. Students, as a digital generation, are a group frequently exposed to such promotional stimuli. To investigate the causal relationship between variables, this study employed a quantitative approach using explanatory research. Data were collected through questionnaires administered to students at the Faculty of Economics and Business, Islamic University of Malang. Multiple linear regression analysis was then used to examine the simultaneous and partial effects of flash sales and free shipping on impulsive buying behavior. The results showed that both promotional tactics had a significant impact on impulse buying, with free shipping increasing perceived transaction value by lowering shipping costs and flash sales stimulating purchases through time pressure and perceived scarcity. It is hoped that this study will theoretically add to knowledge of digital consumer behavior and practically offer guidance to e-commerce professionals and academic institutions on how to improve rational consumption literacy in the digital era. Keywords: Flash Sale, Free Shipping, Impulsive Buying, Consumer Behavior, E-Commerce.